A Survey on the Aspects of Human-Robot Interaction in Autonomous Vehicles - Rosa, Nícolas; Romero, Roseli Ap.; Grassi Jr, Valdir (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
As the technical challenges on intelligent vehicles have been fulfilled, researchers have begun to discuss the social and ethical aspects regarding the development of platforms that allow more interaction between passengers and autonomously driven vehicles. In this context, this paper focuses on the main topics that are currently being studied to improve aspects of this interaction and to design potential new approaches. The main contributions, discussions, concerns, and prospects in the Human-Robot Interaction field for autonomous vehicles are presented, pointing at new directions of research in this area and challenges to be overcome.